Cancer vaccines: platforms and current progress - Wanting Lei; Kexun Zhou; Ye Lei; Qiu Li; Hong Zhu (Molecular Biomedicine)
Abstract Cancer vaccines, crucial in the immunotherapeutic landscape, are bifurcated into preventive and therapeutic types, both integral to combating oncogenesis. Preventive cancer vaccines, like those against HPV and HBV, reduce the incidence of virus-associated cancers, while therapeutic cancer vaccines aim to activate dendritic cells and cytotoxic T lymphocytes for durable anti-tumor immunity. Recent advancements in vaccine platforms, such as synthetic peptides, mRNA, DNA, cellular, and nano-vaccines, have enhanced antigen presentation and immune activation. Despite the US Food and Drug Administration approval for several vaccines, the full therapeutic potential remains unrealized due to challenges such as antigen selection, tumor-mediated immunosuppression, and optimization of delivery systems. This review provides a comprehensive analysis of the aims and implications of preventive and therapeutic cancer vaccine, the innovative discovery of neoantigens enhancing vaccine specificity, and the latest strides in vaccine delivery platforms. It also critically evaluates the role of adjuvants in enhancing immunogenicity and mitigating the immunosuppressive tumor microenvironment. The review further examines the synergistic potential of combining cancer vaccines with other therapies, such as chemotherapy, radiotherapy, and immune checkpoint inhibitors, to improve therapeutic outcomes. Overcoming barriers such as effective antigen identification, immunosuppressive microenvironments, and adverse effects is critical for advancing vaccine development. By addressing these challenges, cancer vaccines can offer significant improvements in patient outcomes and broaden the scope of personalized cancer immunotherapy.